Track Classification and Characteristics Analysis of Northeast China Cold Vortex During the Warm Season - Jin Tong; Yueming Yu; Qiuping Wang; Xulin Ma; Zhaorong Zhuang (Atmosphere)
Understanding the characteristics of the Northeast China Cold Vortex (NCCV) during the warm season (May to September) is essential for enhancing the forecast skills in Northeast China. This study employed ERA5 reanalysis data over 2012–2022 and the optimized K-means clustering algorithm to classify NCCV tracks into five types: (A) eastward-moving dissipative, (B) eastward-moving retrogressive, (C) short-range eastward-moving offshore, (D) long-range eastward-moving offshore, and (E) long-range southeastward-moving offshore. The results demonstrated that variations in circulation configurations governed the tracks of the NCCVs, bringing about the diversity in the center intensity, lifespan, movement speed, and rainstorm probability results. Specifically, the blocking high (BH) over the Sea of Okhotsk served as the primary control system, favoring slow-moving, long-lived NCCVs (type A and type B), which were associated with a higher probability of cold vortex (CV) rainstorms. However, fast-moving, the short-lived NCCVs (type C) had a weaker impact on precipitation. A spatiotemporal analysis further revealed obvious inter-monthly variation in NCCV tracks. From May to August, under the influence of the northward-moving subtropical high and the strengthening of the BH, the occurrence of types A and B increased, while the occurrence of other types decreased. This synoptic shift promoted moisture transport into Northeast China, increasing the frequency of CV rainstorms in July and August.